2007
DOI: 10.1103/physrevlett.98.057401
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determination of a Short-Lived Excited Iron(II) Complex by Picosecond X-Ray Absorption Spectroscopy

Abstract: Structural changes of the iron(II)-tris-bipyridine ( Fe II bpy 3 2 ) complex induced by ultrashort pulse excitation and population of its short-lived ( 0:6 ns) quintet high spin state have been detected by picosecond x-ray absorption spectroscopy. The structural relaxation from the high spin to the low spin state was followed over the entire lifetime of the excited state. A combined analysis of the x-rayabsorption near-edge structure and extended x-ray-absorption fine structure spectroscopy features delivers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
239
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 230 publications
(265 citation statements)
references
References 35 publications
24
239
2
Order By: Relevance
“…Studies by Chergui and co-workers on [Fe(bpy) 3 ] 2+ (where bpy is 2,2'-bipyridine) yielded similar conclusions in terms of extremely rapid formation of the high-spin excited state, 35,36 suggesting that sub-picosecond, formally ∆S = 2 spin-state conversion might be a common feature following charge-transfer excitation of low-spin iron polypyridyl complexes. 37 Transient hard x-ray spectroscopy of the extended x-ray absorption fine structure (EXAFS) at the Fe K-edge of [Fe(tren(py) 3 )] 2+ and similar systems 33,38,39 has revealed detailed structural aspects associated with the MLCT transition, indicating that the electronic changes that follow optical excitation are concurrent with a dilation of the Fe-N bonds of ca. 0.2 Å.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Chergui and co-workers on [Fe(bpy) 3 ] 2+ (where bpy is 2,2'-bipyridine) yielded similar conclusions in terms of extremely rapid formation of the high-spin excited state, 35,36 suggesting that sub-picosecond, formally ∆S = 2 spin-state conversion might be a common feature following charge-transfer excitation of low-spin iron polypyridyl complexes. 37 Transient hard x-ray spectroscopy of the extended x-ray absorption fine structure (EXAFS) at the Fe K-edge of [Fe(tren(py) 3 )] 2+ and similar systems 33,38,39 has revealed detailed structural aspects associated with the MLCT transition, indicating that the electronic changes that follow optical excitation are concurrent with a dilation of the Fe-N bonds of ca. 0.2 Å.…”
Section: Resultsmentioning
confidence: 99%
“…In an X-ray absorption study, Gawelda et al determined the structure of the light-induced ≈ 0.6 nslived excited state of [Fe(bipy) 3 ] 2+ and showed that the structural variations correspond to a 0.2Å elongation of the Fe-N bond length [8], typical for a LS to HS transition in Fe 2+ systems [37]. In our recent extension towards ps time-resolved XES (using a low-repetition pump laser at 1 kHz), we characterized the spin momentum change of the Fe II , which was in a good agreement with the expected ∆S = 2 [33].…”
Section: The High-spin State Of [Fe(bipy) 3 ] 2+ As Reflected By Xesmentioning
confidence: 99%
“…Tools sensitive to the electronic structure and the spin state, which can also be utilized on the femtosecond (fs) to nanosecond (ns) time scales, can shed light on the yet unknown details of the relevant intermediate steps involved in the spin-state switching process. Previously, fs laser spectroscopy has been used for this purpose, which have delivered a rich picture of the ultrafast events taking place on the first few hundred fs [4,5,6,7,8]. These tools are, however, rather insensitive to the changes in the spin state next to the concomitant geometric structure changes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies concerned the structural dynamics of photodissociated intermediates in the solution phase as in the case of NiTPP-L 2 and NiTMP (where TPP = nickel tetraphenylporphyrin, L = piperidine and TMP = tetramesitylporphyrin) [249,250]. Furthermore, TR-XAS was employed to monitor ultrafast spin crossover in iron complexes, unveiling also the structures of elusive high-spin states [160,[251][252][253], as well as to clarify the mechanism of solvent-shell rearrangements around atomic ionic solutes [254].…”
Section: (Py) 2 ] 2+mentioning
confidence: 99%
“…Gawelda et al succeeded in capturing the [Fe(bpy) 3 ] 2+ 5 T 2 ES geometry in aqueous solution, probing the photoprocess with 70 ps hard X-ray pulses [251]. Fe K-edge TR-XAS spectra with ps resolution were collected to follow the structural relaxation from the HS to the LS state over the entire lifetime of the ES.…”
Section: ] 2+mentioning
confidence: 99%